2013
DOI: 10.1016/j.exer.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Time outdoors and the prevention of myopia

Abstract: Recent epidemiological evidence suggests that children who spend more time outdoors are less likely to be, or to become myopic, irrespective of how much near work they do, or whether their parents are myopic. It is currently uncertain if time outdoors also blocks progression of myopia. It has been suggested that the mechanism of the protective effect of time outdoors involves light-stimulated release of dopamine from the retina, since increased dopamine release appears to inhibit increased axial elongation, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
242
2
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(258 citation statements)
references
References 88 publications
5
242
2
9
Order By: Relevance
“…Similarly, some previous studies among Chinese children also showed that there was no significant association or weak association between outdoor activity and myopia. 7,[37][38][39] The different results may be related to 40,41 Consistent with previous findings showing that parental myopia was significantly related to myopia, and illustrating an increased risk of myopia in children with increasing numbers of myopic parents, 13,17,24,28 the current study demonstrated that there was a trend for higher myopia prevalence among children with a parental myopia history. Both male and female students with one myopic parent or two myopic parents were at a higher risk of myopia than those without myopic parents.…”
supporting
confidence: 81%
“…Similarly, some previous studies among Chinese children also showed that there was no significant association or weak association between outdoor activity and myopia. 7,[37][38][39] The different results may be related to 40,41 Consistent with previous findings showing that parental myopia was significantly related to myopia, and illustrating an increased risk of myopia in children with increasing numbers of myopic parents, 13,17,24,28 the current study demonstrated that there was a trend for higher myopia prevalence among children with a parental myopia history. Both male and female students with one myopic parent or two myopic parents were at a higher risk of myopia than those without myopic parents.…”
supporting
confidence: 81%
“…In a recent study, 41 the authors discussed possible mechanisms of this protective effect, and suggested that increased light intensity outdoors results in lightstimulated release of the retinal transmitter dopamine, which is known to be able to reduce axial elongation.…”
Section: Physical Activities and Outdoor Activitiesmentioning
confidence: 99%
“…However, during visual work indoors we tend to look at close objects and require more accommodative power, and therefore the refractive error progresses [1,27,28,29].…”
Section: Discussionmentioning
confidence: 99%